Wounded Inner Child Experiences and Mental Well-Being Among University Students: A Correlational Study - Tasya Aprilya; Gian Sugiana Sugara; Anandha Putri Rahimsyah (Journal of Mental Health and Well-Being in Counseling, 2026)
Wounded inner child and mental well-being are two salient components of psychological health among university students that influence their capacity to adapt to academic demands and the developmental challenges of emerging adulthood. This study aimed to describe the prevalence of wounded inner child experiences among students and to examine their relationship with levels of mental well-being. Employing a correlational quantitative design, the research sampled 272 undergraduates and assessed childhood-derived wounds and mental well-being using standardized instruments. Results indicate a significant negative association between wounded inner child scores and mental well-being (r = –0.469), with the dimensions of shame/low self-worth, suppressed anger, and feelings of unlovability contributing most strongly to reduced well-being. These findings suggest that higher levels of wounded inner child experiences are associated with lower emotional and psychological well-being. Overall, the study underscores the importance of counseling interventions that target emotional wound repair and the strengthening of adaptive capacities to promote student mental-health in higher education settings.